2015
DOI: 10.15406/jaccoa.2015.03.00098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Versus Resistance Training on Blood Pressure in Hypertensive Patients

Abstract: Study Design: Experimental study design.Background: Aerobic training and resistance training are the two treatment technique used in reducing systolic blood pressure, diastolic blood pressure and heart rate. There is limited evidence for comparison of aerobic training and resistance training in reducing systolic blood pressure, diastolic blood pressure and heart rate. Purpose of study:To establish the effect of aerobic training and resistance training on blood pressure in hypertensive patients.Method: Total nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Our findings indicated that all three training groups ATG, RTG, and CTG improved cardiorespiratory (resting heart rate); however, the aerobic training group led to a greater reduction in heart rate. The findings of this study were also supported by previous literatures ( 37 ). They came to the conclusion that patients' blood pressure, and heart rate improvements were statistically significant after six weeks of aerobic training ( 38 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings indicated that all three training groups ATG, RTG, and CTG improved cardiorespiratory (resting heart rate); however, the aerobic training group led to a greater reduction in heart rate. The findings of this study were also supported by previous literatures ( 37 ). They came to the conclusion that patients' blood pressure, and heart rate improvements were statistically significant after six weeks of aerobic training ( 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this study were also supported by previous literatures ( 37 ). They came to the conclusion that patients' blood pressure, and heart rate improvements were statistically significant after six weeks of aerobic training ( 38 ). On the other hand, one study found that aerobic exercise had a significant impact on resting blood pressure and heart rate in prehypertensive and stage 1 hypertensive subjects and that after six weeks of aerobic training, these values significantly decreased in hypertensive individuals ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…Swati and coauthros in their study have compared the effect of 6 weeks aerobic (at 60-70% of maximum HR) and resistance exercise trainings on blood pressure of patients with hypertension. They found that both aerobic and resistance trainings were effective in reducing systolic and diastolic blood pressures and heart rate, while aerobic training was significantly more effective than resistance training [40]. Tsai and coauthors found that low to moderate intensity exercise is effective in lowering blood pressure, and in comparing the effect of different exercise intensities, low intensity exercise was more effective in lowering blood pressure than was high intensity exercise [41].…”
Section: Discussionmentioning
confidence: 99%
“…Tsai and coauthors found that low to moderate intensity exercise is effective in lowering blood pressure, and in comparing the effect of different exercise intensities, low intensity exercise was more effective in lowering blood pressure than was high intensity exercise [41]. The reason is that endurance training has a greater impact on maximum oxygen uptake (VO2 max) and associated cardiopulmonary variables and it more effectively modifies cardiovascular disease risk factors associated with the development of coronary artery disease [40]. In the present study we used moderate intensity endurance training, which showed similar effects on blood pressure, and in addition this effect was augmented when combined with MitoQ administration.…”
Section: Discussionmentioning
confidence: 99%